ANALISIS MINAT BELANJA SKINCARE MAHASISWA JURUSAN MANAJEMEN PASCA HARI LEBARAN - Nazwa Habina Alwi; Seftiana Devi Yanti; Syahputri Anugerah; Aylsa Kamila (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the interest in purchasing skincare products among Management students after the Lebaran holiday period. The research employed a survey method using a questionnaire distributed to 30 active student respondents. The collected data included demographic characteristics, online shopping behavior post-Lebaran, and factors influencing interest in skincare purchases. The results indicate that the majority of respondents were female students under 22 years old who actively shopped online after Lebaran, primarily through Shopee and TikTok Shop platforms. The main factors driving purchase interest were promotional discounts, ease of access, and social media influence. Most respondents made impulsive purchases but showed a tendency to continue online shopping beyond the Lebaran period. This study provides valuable insights for businesses in designing targeted marketing strategies for the student segment, especially during the post-Lebaran period.